Analysis of the Effect of Capital, Length of Business and Number of Customers on Total Income of the Cake Industry in Palangka Raya City - Hema Kartina Br Purba (Fakultas Ekonomi dan Bisnis Universitas Palangka Raya, 2021)
The method used in this study using multiple linear regression analysis method. The type of data used is primary data. Primary data was obtained by giving questionnaires directly to respondents as many as 30 respondents who had been collected and then performed multiple linear regression analysis with income as the dependent variable and capital, length of business and number of customers as independent variables. The results of the analysis in this study show that the Capital variable has a positive and significant effect on the income of the cake industry in Palangka Raya City, while the Business Age variable has a positive and significant effect on the income of the cake industry in Palangka Raya City and the Number of Customers variable has a negative and insignificant effect on industry income. cake in Palangka Raya City